SYNTHESIS, CHARACTERIZATION AND APPLICATION OF GREEN SYNTHESIZED Ag NPs IN ENDODONTIC THERAPY TO REDUCE MICROBIAL BIOFILM - MATTIGATTI, SUDHA; DATKHILE, KAILAS (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Introduction: Green synthesis of Silver Nanoparticles (Ag NPs) by aqueous extract of Nophapodytes foetida plant offers biocompatible and cost-efficient substitute for costly and non-biocompatible chemical reducing agents. Methods: The crude aqueous extract of Nophapodytes foetida plant bark was used with silver nitrate in the volume ratio of 1:2 for synthesis of Ag NPs. The mixture was incubated at 40 °C for 1 hr results into synthesis of Ag NPs, which was further confirmed by characterization. The characterization of Ag NPs was carried out by UV-Vis Spectroscopy, Scanning Tunneling Microscopy (STM) and Scanning Electron Microscopy (SEM) to study optical and morphological characteristics, respectively. Studies were also performed for determination antibacterial activity of Ag NPs against inoculum of Enterococcus faecalis (ATCC: 29212) containing 1⨯105 CFU/ mL by anti-well diffusion assay and broth dilution method. Results: The absorption spectrum of Ag NPs and band gap was found to be at 355 nm and 3.49 eV respectively. Ag NPs showed cluster morphology on surface at 47.2 nm under STM and rough nuggets like morphology of Ag NPs with average size range of 25 to 55 nm under SEM. Conclusion: Ag NPs was found to be effective antibacterial agent at the concentration of 1000 µg/mL against Enterococcus faecalis predominantly present in the root canal and therefore the Ag NPs based intracanal medicaments may have applications in endodontics.